China’s Role in Modern World Politics - Дашко, І. М.; Михайліченко, Л. В. (Київський національний університет імені Тараса Шевченка, 2024)
Annotation. The article examines the role of China in modern world politics. China's share in the world economy in 2022 is analyzed. The key factors that contributed to the country's growth are identified. The dynamics of China's GDP growth in 2010-2022 is studied. China's place in the global competitiveness ranking for 2021-2022 is substantiated. The inflow of FDI is analyzed, which is cyclical in nature, since investments are a direct indicator of crises. It is noted that China's economic expansion is expanding and its influence in the world is increasing due to the formation of dependence on China as both an exporter and an importer. The data of the Global Innovation Index report, where China is among the 20 most innovative countries in the world, are substantiated. The foreign policy of the People's Republic of China is studied and its basic principles are determined. It is substantiated that China has a strong economy and a strong competitive position in the world economy, which allows China to position itself as one of the world leaders in the international arena. The economic power of China is determined. Xi Jinping's foreign policy is substantiated. It is revealed that over the years, China has made significant progress in transforming into a dynamic, knowledge-based economy and has managed to introduce new rules to cope with the governance challenges posed by the onset of the currency crisis, pandemic and the 2022 crisis. It is investigated that China currently accounts for almost a third of world exports and imports. The role of China in world politics is studied on the example of its position on the war in Ukraine and relations with Russia. China's place in the world ranking of countries according to the Innovation Index for 2020-2022 is studied. It is noted that in its foreign policy, China adheres to five basic principles, in particular: mutual respect for territorial integrity and sovereignty, non-aggression, non-interference in the internal affairs of another country, equality and mutual benefit, and peaceful coexistence. The dynamics of Russian exports to China is analyzed.

Анотація. В статті розглянуто роль Китаю у сучасній світовій політиці. Досліджено частку Китаю у світовій економіці. Визначено ключові фактори, які сприяли росту країни. Досліджено динаміку росту ВВП Китаю. Обґрунтовано місце Китаю у рейтингу глобальної конкурентоспроможності. Проаналізовано приплив ПІІ. Зазначено про розширення економічної експансії КНР та збільшення впливу в країнах світу через формування залежності від Китаю як від експортера так і від імпортера одночасно. Обґрунтовано дані звіту Глобального Індексу інновацій. Досліджено зовнішню політику КНР та визначені її основні принципи. Обґрунтовано, що Китай має сильну економіку та сильну конкурентну позицію у світовій економіці. Визначено економічну міць Китаю. Обґрунтовано зовнішню політику Сі Цзіньпіна. Виявлено, що за роки свого існування Китай домігся значного прогресу в перетворенні в динамічну, засновану на знаннях економіку. Досліджено, що в даний час на Китай припадає практично третина світового експорту та імпорту. Досліджено роль Китаю у світовій політиці на прикладі його позиції щодо війни в Україні та відносин з РФ. Досліджено місце Китаю у рейтингу країн світу за Індексом інновацій. Зазначено, що у своїй зовнішній політиці КНР дотримується п’ятьох основних принципів, зокрема: взаємна повага до територіальної цілісності та суверенітету, ненапад, невтручання у внутрішні справи іншої країни, рівність та взаємна вигода й мирне співіснування. Проаналізовано динаміку експорту РФ до Китаю.
Роль Китаю у сучасній світовій політиці
Keywords: China; expansion; foreignpolicy; GDP; exports; imports; geopolitics; worldpolitics; strategy; war; КНР; експансія; зовнішняполітка; ВВП; експорт; імпорт; геополітика; світоваполітика; стратегія; війна